Effect of Different Photo Periods on the Biological Parameters of Chrysoperla carnea under Laboratory Conditions - Qadeer Ahmed; Raza Muhammad; Nazir Ahmad; Javed Ahmed; Shahnaz Naz; Hayder Ali; Nazia Suleman (Journal of Basic & Applied Sciences, 2012)
Many insects are known to give response in adaptive way for seasonal changes in day lengths. Photoperiod control’s many developmental responses and allows insects to survive periods of unfavorable environmental conditions. An experiment was conducted to study the effect of different photoperiod lengths on biological parameters of green lacewing, Chrysoperla carnea. Four different photoperiod regimes were selected with varying lengths of light/dark hours (8/16, 10/14, 24/0 and 0/24) at a constant 26±2°C temperature with 70 % RH (relative humidity) in the laboratory. Photoperiod regimes affected the development of C. carnea from egg to adult. In complete darkness (L: 0 D: 24), minimum egg laying, hatching, larval survival and adult emergence were recorded. Incubation period for eggs, larval period and pupal duration were also significantly longer in complete darkness as compared to other treatments 8L: 16D and 10L: 14D. Whereas, the treatment with complete light hours (L: 24, D: 0) resulted in maximum egg laying hatching, larval survival and adult emergence. The incubation period for eggs, larval and pupal duration significantly shortened as compared to other treatments.Sex ratios skewed towards female when full light hours were provided for development.